Extracranial Carotid Disease: Update on Management Strategies for the Asymptomatic and Symptomatic - Vinall, Phil (MD Conference Express, 2009)
The consensus among presenters in this session was that although carotid endarterectomy (CEA) remains the most often used and the gold standard for treating carotid stenosis, 30-day stroke/death risks appear to be comparable between carotid artery stenting and CEA. This article discusses the NASCET, ESCT, and VA Trial, along with improvements in stenting outcomes and the need for aggressive treatment for transient ischemic attack.